Digitalizing an integrated logistics flows of a focus enterprise - A. P. Tyapukhin; V. S. Starodubtsev (Вестник университета)
The purpose of the study is to clarify and supplement the theory and methodology of design, formation, and optimization of management of integrated, homogeneous, and heterogeneous ﬂows of material, information, ﬁnancial, and human resources in channels, chains, fronts, echelons, and networks of various types. The descriptor and facet classiﬁcation methods and methods of analysis and synthesis, induction and deduction have been chosen as research methods, and binary matrices formed on the basis of qualitative attributes and dichotomies of objects and components of integrated logistics ﬂows management were used as tools. The variants of business system management subjects and objects integration have been substantiated. An end-to-end classiﬁcation of enterprises and relations among them, processes, and logistics operations has been developed for the purpose of digitalization of integrated logistics ﬂows and business systems of various types. The variants of these ﬂows have been deﬁned and digitized, and theoretical and methodological prerequisites for modeling these ﬂows have been created. The value of the study lies in theoretical and methodological prerequisites creation for digitalization of non-physical subjects and objects of integrated logistics ﬂows management, as well as their integration with other physical subjects and objects in order to develop rational management decisions both at the level of links and at the level of the business system.